2014
DOI: 10.1136/bjophthalmol-2013-304823
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of parafoveal cone density measurements

Abstract: BackgroundAdaptive optics scanning light ophthalmoscopy (AOSLO) enables direct visualisation of the cone mosaic, with metrics such as cone density and cell spacing used to assess the integrity or health of the mosaic. Here we examined the interobserver and inter-instrument reliability of cone density measurements.MethodsFor the interobserver reliability study, 30 subjects with no vision-limiting pathology were imaged. Three image sequences were acquired at a single parafoveal location and aligned to ensure tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…The large variability in cone density at a given location on the retina is known to depend upon meridian, age, eye length/refractive error, and health of the retina measured in numerous laboratories with in vivo methods (Song, Chui, & Zhong et al, 2011; Chui, Song, & Burns 2008a; Chui, Song, & Clark et al, 2012; Liu, Tarima, & Visotcky et al, 2014; Obata & Yanagi, 2014; Li, Tiruveedhula, & Roorda, 2010; Park, Chung, & Greenstein et al, 2013; Obata & Yanagi, 2014; Tan, Wright, & Rajendran et al, 2015) as well as with ex vivo methods (Curcio, Sloan, & Kalina et al,1990; Ahnelt,1998). However, our results indicate that the variability of total cones across a large portion of the macula is much less among individuals, when the eye is healthy, eye length is normal, and age is restricted to young adult ages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large variability in cone density at a given location on the retina is known to depend upon meridian, age, eye length/refractive error, and health of the retina measured in numerous laboratories with in vivo methods (Song, Chui, & Zhong et al, 2011; Chui, Song, & Burns 2008a; Chui, Song, & Clark et al, 2012; Liu, Tarima, & Visotcky et al, 2014; Obata & Yanagi, 2014; Li, Tiruveedhula, & Roorda, 2010; Park, Chung, & Greenstein et al, 2013; Obata & Yanagi, 2014; Tan, Wright, & Rajendran et al, 2015) as well as with ex vivo methods (Curcio, Sloan, & Kalina et al,1990; Ahnelt,1998). However, our results indicate that the variability of total cones across a large portion of the macula is much less among individuals, when the eye is healthy, eye length is normal, and age is restricted to young adult ages.…”
Section: Discussionmentioning
confidence: 99%
“…Cone density measured in vivo by using adaptive optics to correct for the ocular aberrations of the human eye, along with highly magnified retinal images, has large inter-individual variations not due to methodological considerations, particularly varying with aging (Song, Chui, & Zhong et al, 2011; Chui, Song, & Burns 2008a; Chui, Song, & Clark et al, 2012; Liu, Tarima, & Visotcky et al, 2014; Obata & Yanagi, 2014). At the fovea, individual differences in young, healthy eyes are reported to have a range of 1.81:1 (Zhang, Godara, & Blanco et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Chiu et al ( 2013) demonstrated similar repeatability using the same data set and a fully automatic algorithm based on graph theory and dynamic programming. Most recently, we examined the inter-observer and inter-instrument reliability of cone density measurements and found that the inter-observer study’s largest contribution to variability was the subject (95.72%) while the observer’s contribution was only 1.03% (Liu et al 2014). For the inter-instrument study, we reported an average cone density ICC of between 0.931 and 0.975 (Liu et al 2014).…”
Section: Xx1 Introductionmentioning
confidence: 99%
“…Secondly, the repeatability and reproducibility measurements were performed by an expert who was proficient in both acquiring OCT images and generating en face images. For other observers, the repeatability and reliability of this technique may be worse (Bartlett and Frost 2008; Liu et al 2014). Finally, our analysis was limited to the UV-cone submosaic- as other submosaics are more difficult to visualize (Huckenpahler et al 2016); thus our results should not be assumed to apply to the R/G- or S-cone submosaic.…”
Section: Discussionmentioning
confidence: 99%